2018
DOI: 10.1093/aje/kwy259
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Factors, Exogenous Hormone Use, and Risk of B-Cell Non-Hodgkin Lymphoma in a Cohort of Women From the European Prospective Investigation Into Cancer and Nutrition

Abstract: The role of hormonal factors in the etiology of lymphoid neoplasms remains unclear. Previous studies have yielded conflicting results, have lacked sufficient statistical power to assess many lymphoma subtypes, or have lacked detailed information on relevant exposures. Within the European Prospective Investigation Into Cancer and Nutrition cohort, we analyzed comprehensive data on reproductive factors and exogenous hormone use collected at baseline (1992-2000) among 343,458 women, including data on 1,427 incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…However, females had comparatively higher APC than males for age-adjusted leukemia incidence during the entire monitoring period. The potential reasons for the sex difference in leukemia incidence maybe originate from female reproductive factors, exogenous hormones, and lifestyles, affecting potentially immune function and the carcinogenesis process 24 - 26 . However, we observed that the 5-year survival rate of all leukemia patients did not differ in sex throughout the monitoring period.…”
Section: Discussionmentioning
confidence: 99%
“…However, females had comparatively higher APC than males for age-adjusted leukemia incidence during the entire monitoring period. The potential reasons for the sex difference in leukemia incidence maybe originate from female reproductive factors, exogenous hormones, and lifestyles, affecting potentially immune function and the carcinogenesis process 24 - 26 . However, we observed that the 5-year survival rate of all leukemia patients did not differ in sex throughout the monitoring period.…”
Section: Discussionmentioning
confidence: 99%
“…Costas et al observed a significantly higher risk of B-cell NHL in women who underwent hysterectomy and bilateral oophorectomy than in women who did not, supporting the role of oestrogens. 33 In addition, more TB-infected men present clinical symptoms than women. 34 However, a large sample prospective cohort study is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…While malignant melanoma is the most common cancer arising during pregnancy, accounting for about a third of malignancies among expectant mothers, parous women are not at higher risk of subsequently developing melanoma than nulliparous women (51), or of developing non-melanoma skin cancer (52). Women have a lower incidence of leukemias and lymphomas overall than men, but there is little evidence that pregnancy factors are associated with non-Hodgkin's lymphoma (53). One study, however, showed that parous women had about a two-and-a-half-fold increased risk of lymphoid neoplasm compared with nulliparous women, but no associations were observed between lymphoid neoplasms and other reproductive factors, including age at first birth and breastfeeding (54).…”
Section: Leukaemia/lymphoma Sarcomas and Other Solid Tumoursmentioning
confidence: 99%